Hyperon physics at BESIII - Viktor Thorén (SciPost Physics Proceedings, 2024)
Spin polarization and entanglement are utilized by the BESIII experiment to learn more about the production and decay properties of hyperon-antihyperon pairs in a series of recent analyses of its unprecedented datasets at the $J/\psi$ and $\psi'$ resonances. This has lead to the observation of significant transverse polarisation in decays of $J/\psi$ or $\psi'$ into $\Lambda \bar{\Lambda}$, $\Sigma \bar{\Sigma}$, $\Xi \bar{\Xi}$, and $\Omega \bar{\Omega}$. Because of the non-zero polarization, the decay parameters for the most common hadronic weak decays of both hyperons and antihyperons could be determined independently for the first time. Comparing these to each other yields precise tests of direct, $\Delta S = 1$ CP-violation that complement measurements of kaon decays.